A study of the impact of technological innovations on the social sustainability of facilities management employees in South Africa - Adama, Unekwu Jonathan (Department of Construction Economics and Management, 2020)
This research investigates the impact of technological innovations (TIs) on the social sustainability of facilities management (FM) employees in South Africa. The rationale for the study is that no empirical evidence shows how the adoption of TIs impacts the social sustainability of FM employees. The study adopts the sequential mixed-methodology approach. The quantitative phase makes use of a questionnaire survey which formed the foundation for the qualitative interview phase. The relative importance index (RII) is used to analyse different questions, such as (1) the factors influencing the adoption of TIs in FM organisations (2) the impact of the TIs on FM practice, (3) the localisation of the employee social sustainability factors and (4) the determination of the impact of TIs on the social sustainability of FM employees. An Interpretive Structural Model (ISM) approach is used to determine which social sustainability factor(s) should be prioritised while promoting the social sustainability of the FM employees. The findings of this study show that cloud-based TIs, ICT-based TIs and sensor-based TIs are the most popular in FM organisations in South Africa. Furthermore, the impact of TIs on the core business factors in FM organisations have a mean score of between 3.00 to 3.19 depending on the factor of interest. The RII analysis led to the development of the initial FM employee social sustainability framework which identified “job security”, “remuneration” and “professional status” as the three most important FM employee social sustainability factors. However, the ISM analysis which considered hierarchy, driving power and dependence of the factors identified “organisation policy” as main factor in level five that drives other employee social sustainability factors. Furthermore, “overwork”, “autonomy”, “interpersonal relationship”, “work and home-life balance” and “retirement development plan” were the root factors in level four that must be prioritised by facilities managers to promote employee social sustainability. The study contributes to knowledge by identifying the most popular TIs that are adopted by FM organisations in South Africa, and determining the interrelationship, hierarchical importance and dependences of the various employees’ social sustainability factors in FM organisations. Through the development of the framework for FM employee social sustainability, facilities managers have the knowledge of the factors to prioritise when they need to promote the social sustainability of their employees. The study recommends that FM organisation policies on TI adoption must align with the overall socio-economic wellbeing program to contribute to social sustainability in South Africa.